2010
DOI: 10.1002/dc.21486
|View full text |Cite
|
Sign up to set email alerts
|

Divide and rule: Cytodiagnosis of thyroid lesions using pattern analysis: A study of 233 cases

Abstract: Fine needle aspiration cytology (FNAC) of the thyroid is a simple, accurate, fast, economical and safe method for the diagnosis of thyroid lesions on FNA. The objective of this study was application of pattern analysis in the interpretation of thyroid lesions. Two hundred and thirty three cases of thyroid lesion were reviewed, which had histopathological correlation. Smears were classified based on primary (predominant) and secondary (next dominant) pattern and categorized. The variation between combined and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Layfield et al, Ohori et al, Muddegowda et al, and Shi et al have reported low reproducibility for AUS/FLUS, with marked interobserver and intraobserver variations. 15,16,30,31 The level of experience of the clinician/pathologist performing the thyroid FNA, the methods used for specimen preparation and staining, the number of FNA passes performed, and the availability of onsite rapid interpretation may all be contributing factors to this variation. The publication of reference images and text for TBSRTC, both in print and on the Internet (available at: www.papsociety.org), will inevitably promote greater uniformity.…”
Section: Aus/flus Usementioning
confidence: 99%
“…Layfield et al, Ohori et al, Muddegowda et al, and Shi et al have reported low reproducibility for AUS/FLUS, with marked interobserver and intraobserver variations. 15,16,30,31 The level of experience of the clinician/pathologist performing the thyroid FNA, the methods used for specimen preparation and staining, the number of FNA passes performed, and the availability of onsite rapid interpretation may all be contributing factors to this variation. The publication of reference images and text for TBSRTC, both in print and on the Internet (available at: www.papsociety.org), will inevitably promote greater uniformity.…”
Section: Aus/flus Usementioning
confidence: 99%
“…Two schools of thought have emerged—one proposes to eliminate the FLUS category (or combine the FLUS and FN categories to form a five‐tiered system) and the other suggests a further subdivision of FLUS into categories with different risk assignments . Related issues involve determining whether nuclear atypia or architectural atypia (microfollicles) in an FNA is more reliably predictive of malignancy, quantifying the amount or extent of a “diagnostic” feature that should be required for inclusion in the suspicious for malignancy category, assessing the value of repeat FNA in nodules reported as FLUS and FN nodules, requiring consensus review before a thyroid FNA is diagnosed as FLUS, and assessing the potential role of molecular studies as an adjunct to cytodiagnosis . This study was designed to determine if cytomorphology could help further stratify lesions that are currently being reported as FLUS.…”
mentioning
confidence: 99%
“…Low reproducibility for AUS/FLUS has been reported, variability in criteria used for AUS/FLUS is responsible for significant interobserver and inter‐institutional variation in making diagnoses. In our study also poor interobserver agreement level ( K = 0.1301) was observed in the AUS/FLUS category; however, our sample size for AUS, 12, was small.…”
Section: Discussionmentioning
confidence: 99%